Study of the Digital Geological Compass in Increasing the Effectiveness and Efficiency of Measuring Geological Structure Data in the Field - Hendrawan, Rezki Naufan; Irsyad, Muhammad; Gunawan, Aditya; Zainuddin, Ahmad Dennil; Widiatama, Angga Jati (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
This study compares the use of analog geological compasses and digital geological compasses in measuring fracture planes on crystalline rocks at the Lampung region. The measurement results demonstrate that using digital compasses yields higher time efficiency than analog compasses, with a reduction in measurement duration of over 50%. Although the dominant directions of the fracture planes were similar between the two methods, the inclination values and accuracies of each plane were not always consistent. Data processing using rose diagrams and stereonets indicates that the RockD application provides comparable results to measurements obtained using analog compasses. Therefore, the use of digital compass applications such as RockD can serve as an efficient alternative for geologists in collecting field data related to rock fractures, particularly in the context of quantitative data. However, analog geological compass is still recommended for measuring planes with on single-plane characteristics, such as rock bedding and fault mirrors. This study demonstrates the potential for development and transformation from analog geological compasses to digital geological compasses, and further research is needed to investigate the minimum number of fractures that can be measured with a digital geological compass to be considered statistically valid.